A phase Ib study of the combination regorafenib with PF-03446962 in patients with refractory metastatic colorectal cancer (REGAL-1 trial) - Clarke, Jeffrey Melson (Cancer Chemother Pharmacol, 2019)
PURPOSE: This study aimed to evaluate the maximum tolerated dose (MTD) and recommended phase II dose (RPTD), as well as the safety and tolerability of PF-03446962, a monoclonal antibody targeting activin receptor like kinase 1 (ALK-1), in combination with regorafenib in patients with refractory metastatic colorectal cancer. METHODS: The first stage of this study was a standard “3 + 3” open-label dose-escalation scheme. Cohorts of 3–6 subjects were started with 120 mg of regorafenib given PO daily for 3 weeks of a 4 week cycle, plus 4.5 mg/kg of PF-03446962 given IV every 2 weeks. Doses of both drugs were adjusted according to dose-limiting toxicities (DLT). Plasma was collected for multiplexed ELISA analysis of factors related to tumor growth and angiogenesis. RESULTS: Seventeen subjects were enrolled, of whom 11 were deemed evaluable. Seven subjects were enrolled at dose level 1, and four were enrolled at level − 1. Overall, three DLTs were observed during the dose-escalation phase: two in level 1 and one in level − 1. A planned dose-expansion cohort was not started due to early termination of the clinical trial. Common adverse events were infusion-related reaction, fatigue, palmar-plantar erythrodysesthesia syndrome, abdominal pain, dehydration, nausea, back pain, anorexia, and diarrhea. One subject achieved stable disease for 5.5 months, but discontinued treatment due to adverse events. CONCLUSIONS: The regimen of regorafenib and PF-03446962 was associated with unacceptable toxicity and did not demonstrate notable clinical activity in patients with refractory metastatic colorectal cancer.